1995
DOI: 10.1159/000173895
|View full text |Cite
|
Sign up to set email alerts
|

Dibutyryl Cyclic Adenosine Monophosphate Stimulates the Sodium Pump in Rabbit Renal Cortical Tubules

Abstract: The elevation in oxygen consumption (QO2) observed following addition of the sodium ionophore nystatin in suspensions of rabbit renal proximal tubules was significantly increased by 1 mM dibutyryl cyclic adenosine monophosphate (db-cAMP). The QO2 after subsequent addition of strophanthidin to block the sodium pump was unnaffected by db-cAMP. However, 10 µM forskolin in the presence of 100 µM IBMX had no significant effect on the QO2 observed following addition of either nystati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…These results indicated that PKA activation led to the stimulation of Na+,K+-ATPase in rat cortical renal cells. This finding is in agreement with recent studies showing a stimulatory effect of cAMP on proximal Na+,K+-ATPase activity estimated by oxygen consumption [12], basolateral membrane potential variation [3] or Na +,K +-ATPase [y-32p]ATP hydrolytic activity [13]. The increases in ion transport activity and in the degree of phosphorylation of the Na+,K+-ATPase suggest that cAMP modulates the enzyme activity by promoting the phosphorylation of its c~-subunit.…”
Section: Resultssupporting
confidence: 94%
“…These results indicated that PKA activation led to the stimulation of Na+,K+-ATPase in rat cortical renal cells. This finding is in agreement with recent studies showing a stimulatory effect of cAMP on proximal Na+,K+-ATPase activity estimated by oxygen consumption [12], basolateral membrane potential variation [3] or Na +,K +-ATPase [y-32p]ATP hydrolytic activity [13]. The increases in ion transport activity and in the degree of phosphorylation of the Na+,K+-ATPase suggest that cAMP modulates the enzyme activity by promoting the phosphorylation of its c~-subunit.…”
Section: Resultssupporting
confidence: 94%
“…Our results are in agreement with studies demonstrating a stimulatory effect of cAMP on proximal tubule Na + ,K + ‐ATPase activity measured in intact cells by (a) ouabain‐sensitive oxygen consumption (Beck et al 1995), (b) Na + ,K + ‐ATPase‐dependent basolateral membrane potential variation (Breton et al 1994), (c) ouabain‐sensitive 8 6 Rb + uptake (Carranza et al 1996), or in permeabilized isolated PCTs (Bertorello & Aperia, 1988, 1989) and kidney cortex homogenate (Giesen et al 1984) by the hydrolytic activity of the enzyme. However, one study has reported inhibition of Na + ,K + ‐ATPase by db‐cAMP (Ribeiro & Mandel, 1992) while another one did not find any effect of either exogenous or endogenous cAMP on Na + ,K + ‐ATPase activity (Satoh et al 1993).…”
Section: Discussionsupporting
confidence: 92%
“…In PCT, short‐term stimulation of Na + ,K + ‐ATPase by conditions that activate PKA has been reported by several groups (Giesen et al 1984; Bertorello & Aperia, 1988; Breton et al 1994; Beck et al 1995; Carranza et al 1996) but the mechanisms have yet to be determined. Besides the possibility of an increase in Na + ,K + ‐ATPase activity due to the kinetic effect of a rise in intracellular Na + concentration (Skou, 1965), a change in the intrinsic properties of Na + ,K + ‐ATPase (Féraille et al 1995) or an increased number of active Na + ‐K + pump units expressed in plasma membranes (Hundal et al 1992) may explain the effect of PKA activation.…”
mentioning
confidence: 99%
“…Evidence suggests that ␤-adrenergic signaling promotes Na excretion by facilitating a blood-lumen flux of Na ϩ , 20 whereas other studies have indicated that ␤-adrenergic signaling inhibits Na ϩ uptake in tubules by stimulating basolateral Na/K ATPase. [22][23][24] Additional renal effects of rolipram that have been reported include regulation of the osmotic permeability response to antidiuretic hormone in neonatal tubules 25 and renin release from juxtaglomerular cells. 26 Both the Dahl SS rats and SHRs are generally considered to be models of renal hypertension.…”
Section: Discussionmentioning
confidence: 99%